If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7r + 6t = -16 Solving -7r + 6t = -16 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-6t' to each side of the equation. -7r + 6t + -6t = -16 + -6t Combine like terms: 6t + -6t = 0 -7r + 0 = -16 + -6t -7r = -16 + -6t Divide each side by '-7'. r = 2.285714286 + 0.8571428571t Simplifying r = 2.285714286 + 0.8571428571t
| 11+18b=19b | | 9=0.5(-9.81)(x^2) | | -9y+5=-7-7y | | -5v-4=-7v | | 53a-55=42 | | -(q+10)=-20 | | =x^2+20x-19 | | 10p-18p+-14=18 | | -30=-2(3c-7) | | x+x-30=2x | | -9-6q=6-9q | | 2w+9ifw=15 | | 3v-12=4v | | 8(1r-12d)= | | -19+3g=5g+17 | | d/3−6=19 | | 5q+7=34 | | 10-14j=-12j | | 3g+-7=8 | | -1y^2-3=-y^2-y-3 | | -4(k-17)=0 | | 0.08x+0.11(3x+37000)=18290 | | 12d+6=9d | | -9-4K=-1-5k | | 1x/2x-1/10x=1/5-1/4 | | 4p=6p-16 | | -3(m-12)=-12 | | 81*.15= | | 12+c=-2c | | -4(x-3)=x | | -16k=-15k-16 | | -4n+5=13 |